Changes of lipoperoxidation and antioxidant system in pariodontal tissues in experimental bronchial asthma under conditions of chronic periodonitis and correction of these changes with thiotriazoline - Reheda, Mykhailo; Shchepanskyi, Borys (Journal of Education, Health and Sport, 2018)
We have analyzed the results of the research of changes in indices of lipid peroxidation (conjugated dienes and malondialdehide) and antioxidant (superoxide dismutase, catalase, ceruloplasmin) systems in guinea pigs’ periodontal soft tissues in experimental bronchial asthma in the dynamics of asthma under conditions of chronic periodontitis and correction of these changes with thiotriazoline. The research was conducted on 50 male guinea pigs weighting 250-270 g, divided into 5 groups: I – intact guinea pigs (n=10), II – guinea pigs (n=10) with asthma under conditions of chronic periodontitis before correction (4th day), III - guinea pigs (n=10) with asthma under conditions of chronic periodontitis before correction (18th day), IV - guinea pigs (n=10) with asthma under conditions of chronic periodontitis before correction (25 th day), V - guinea pigs (n=10) with asthma under conditions of chronic periodontitis after correction (25th day). The results of experimental studies showed the significant increase of conjugated dienes and malondialdehide levels in animal’s periodontal soft tissues at all observed stages of asthma development under conditions of chronic periodontitis before the correction as compared with control group. Intensive synthesis of LPO’s products caused increase on 4th day with further decrease on 18th and 25th days of activity levels of superoxide dismutase, catalase and ceruloplasmin in animal’s periodontal soft tissues before the correction as compared with indices of the control group. After correction with thiotriazoline the the results showed decrease of indices of LPO and increase of activity levels of antioxidant enzymes.